Financial Development and Intersectoral Allocation: A New Approach - FISMAN, RAYMOND; LOVE, INESSA (Journal of Finance, 2004)
ABSTRACT This paper uses a new methodology based on industry comovement to examine the role of financial market development in intersectoral allocation. Based on the assumption that there exist common global shocks to growth opportunities, we hypothesize that country pairs should have correlated patterns of sectoral growth if they are able to respond to these shocks. Consistent with financial markets promoting responsiveness to shocks, countries have more highly correlated growth rates across sectors when both countries have well‐developed financial markets. This effect is stronger between country pairs at similar levels of economic development, which are more likely to experience similar growth shocks.